FILM DOKUMENTER “YANG TERJERAT JALA” (FILM DOKUMENTER MASYARAKAT PEDULI LINGKUNGAN DI PESISIR PANTAI SURABAYA) - Clara Bella Julia (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2018)
The vast seas of Indonesia made the citizen of Indonesia to live in the beaches and make use of the sea products. But Waste which still are the unsolved problems, affected the number of fishes catched. In this piece of creation, the creator will show the condition of the waste problem in the coastlines of surabaya, as well as the explanations from the experts. The targets of this film are individuals of all ages especially teenagers and adults. The creator wishes by the existance of this movie, can lead people to care more about the environment.